The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/oemed-2018-105054
|View full text |Cite
|
Sign up to set email alerts
|

Association between benzene and congenital anomalies in Oklahoma, 1997–2009

Abstract: Objectives: Although the most common cause of death in infants, little is known about the etiology of congenital anomalies. Recent studies have increasingly focused on environmental exposures, including benzene. While benzene is known to affect the central nervous system, the effects on the developing fetus are unclear. Methods: We conducted a retrospective cohort study to evaluate the association between ambient benzene exposure and the prevalence of congenital anomalies among 628,121 singleton births in Ok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A study conducted in Oklahoma evaluated the association between benzene exposure and congenital anomalies. However, their findings did not find an association between benzene exposure during pregnancy and the occurrence of CHDs in offspring (Janitz et al 2018 ). This is similar to our results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study conducted in Oklahoma evaluated the association between benzene exposure and congenital anomalies. However, their findings did not find an association between benzene exposure during pregnancy and the occurrence of CHDs in offspring (Janitz et al 2018 ). This is similar to our results.…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have evaluated the association between benzene and nonisolated pulmonary atresia (Tanner et al 2015 ), cleft palate (Ramakrishnan et al 2013 ), and major congenital, and neural crest malformations (Janitz et al 2018 ; Wennborg et al 2005 ). Some studies have shown that exposure to a mixture of benzene, toluene, ethylbenzene, and xylene (BTEX) compounds during pregnancy may lead to premature birth (PTB) in pregnant women (Cassidy-Bushrow et al 2021a ; Santos and Nascimento 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fusion of several structures and processes of the neonatal face result in the development of both the lip and palate between the 4th and 12th week of gestation. A failure of fusion due to genetic or environmental causes may lead to the development of cleft lip and palate 15 …”
Section: Discussionmentioning
confidence: 99%
“…A failure of fusion due to genetic or environmental causes may lead to the development of cleft lip and palate. 16 ABG forms a fundamental component of the treatment protocol of alveolar clefts in patients with cleft lip and palate. The main objectives of ABG are to: establish continuity of the dental arch, facilitate closure of oro-nasal fistulae, correction of the nasal alar bases and to provide solid bone for tooth migration and dental implant placement.…”
Section: Discussionmentioning
confidence: 99%